Regulatory T-Cells: Potential Regulator of Tissue Repair and Regeneration - Li, Jiatao; Tan, Jean; Martino, Mikaël M.; Lui, Kathy O. (Frontiers in Immunology, 2018)
The identification of stem cells and growth factors as well as the development of biomaterials hold great promise for regenerative medicine applications. However, the therapeutic efficacy of regenerative therapies can be greatly influenced by the host immune system, which plays a pivotal role during tissue repair and regeneration. Therefore, understanding how the immune system modulates tissue healing is critical to design efficient regenerative strategies. While the innate immune system is well-known to be involved in the tissue healing process, the adaptive immune system has recently emerged as a key player. T-cells, in particular regulatory T-cells (Treg), have been shown to promote repair and regeneration of various organ systems. In this review, we discuss the mechanisms by which Treg participate to the repair and regeneration of skeletal and heart muscle, skin, lung, bone, and the central nervous system.